Front Cover: Formation of Layer‐by‐Layer Assembled Cocatalyst Films of S2−‐Stabilized Ni3S4 Nanoparticles for Hydrogen Evolution Reaction (ChemNanoMat 10/2017). Issue 10 (27th September 2017) - Kim, Sungwon; Nishino, Toshio; Saruyama, Masaki; Sakamoto, Masanori; Kobayashi, Hiroyuki; Akiyama, Seiji; Yamada, Taro; Domen, Kazunari; Teranishi, Toshiharu
Abstract : Ni3 S4 nanoparticles are a potential candidate as an electrocatalyst and a photocatalyst for hydrogen evolution reaction. Films of S 2– ‐stabilized Ni3 S4 nanoparticles can be assembled on fluorine‐doped tin oxide electrodes and photoelectrodes by a layer‐by‐layer (LbL) process with metal cation linkers under mild conditions. For both electrodes, the LbL assembled films showed higher photocurrents and current densities with increasing light irradiation time. This LbL assembly process could be applicable to forming ligand‐free and robust nanoparticle films for many types of photoelectrodes without deteriorating their intrinsic optical properties. More information can be found in the Full Paper by T. Teranishi et al. onpage 764 in Issue 10, 2017 (DOI:10.1002/cnma.201700220 ).